Discharge parameters of magnetoplasma compressor: effect of external axial magnetic field - Solyakov, D.G.; Volkova, Yu.Ye.; Marchenko, A.K.; Ladygina, M.S.; Staltsov, V.V.; Petrov, Yu.V.; Chebotarev, V.V.; Merenkova, T.M.; Makhlaj, V.A.; Yeliseyev, D.V. (Вопросы атомной науки и техники, 2020)
This paper reports the findings of our recent experiments on the evaluation of the external axial magnetic field effect on the discharge parameters of a magnetoplasma compressor (MPC). The discharge-voltage characteristics were obtained for varied magnitudes of an external axial magnetic field produced by a solenoid installed on the accelerating channel. Present experiments were carried out with helium (at the initial pressures of 2 and 10 Torr) and argon (at the initial pressure of 1 Torr) as working gases at different initial voltages. The external magnetic field varied up to 0.4 T. The discharge-voltage characteristics can be altered by the magnitude of the external magnetic field, as well as by the geometrical properties of an accelerating channel. Наведено результати експериментів з вивчення впливу зовнішнього поздовжнього магнітного поля на параметри розряду магнітоплазмового компресора (МПК). Вольт-амперні характеристики було отримано для різних значень зовнішнього поздовжнього магнітного поля, що створюється соленоїдом, який встановлено на прискорювальному каналі МПК. Експерименти було проведено з використанням гелію (за початкового тиску від 2 до 10 Торр) та аргону (за початкового тиску 1 Торр) у якості робочих газів за різних значень початкової напруги. Зовнішнє магнітне поле змінювалося до 0,4 Тл. Вольт-амперні характеристики можуть змінюватися залежно від величини зовнішнього поздовжнього магнітного поля, а також від геометричних параметрів прискорювального каналу. Представлены результаты экспериментов по изучению влияния внешнего продольного магнитного поля на параметры разряда магнитоплазменного компрессора (МПК). Вольт-амперные характеристики были получены для разных значений внешнего продольного магнитного поля, которое создаётся соленоидом, установленным на ускорительный канал МПК. Эксперименты проводились с использованием гелия (при начальном давлении от 2 до 10 Торр) и аргона (при начальном давлении 1 Торр) в качестве рабочих газов при разных начальных напряжениях. Внешнее магнитное поле менялось до 0,4 Тл. Вольт-амперные характеристики могут меняться в зависимости от величины внешнего продольного магнитного поля, а также от геометрических параметров ускорительного канала.